Study of the Variety of Local Snacks and Pastries in Medan City: Uniqueness, Preferences, and Culinary Culture - Indra, Febryola; Sitorus, Nova Bernedeta; Maleachi, Sandra; Pramono, Rudy; Valensky, Sherla (Akademi Komunitas MAPINDO, 2024)
The study titled